C—Br…S halogen bonds in novel thiourea N‐oxide cocrystals: analysis of energetic and QTAIM parameters. Issue 2 (29th January 2020) - Wzgarda-Raj, Kinga; Rybarczyk-Pirek, Agnieszka J.; Wojtulewski, Sławomir; Palusiak, Marcin
Abstract : In the crystal structures of crystals of thiourea with 4‐nitropyridine N ‐oxide and 3‐bromopyridine N ‐oxide, both molecular components are linked by N—H…S or N—H…O hydrogen bonds and C—Br…S halogen bonds. The latter interactions were characterized by quantum chemistry (QTAIM) methods and the atoms in molecules (AIM) approach. Abstract : Cocrystals of thiourea with 4‐nitropyridine N ‐oxide, C5 H4 N2 O3 ·2CH4 N2 S, (I ), and 3‐bromopyridine N ‐oxide, C5 H4 BrNO·CH4 N2 S, (II ), crystallize in the monoclinic space group P 21 / c . In the crystals, molecules of both components are linked by N—H…O hydrogen bonds, creating R 2 1 (6) synthons. The bromine substituent of the N ‐oxide component in (II ) is a centre for C—Br…S halogen bonding to the thiourea molecule. Computations based on quantum chemistry methods (quantum theory of atoms in molecules, QTAIM) and atoms in molecules (AIM) theory were performed for a more detailed description of the observed type of halogen‐bonding interaction.